Immediate and short‐term effects of Gufoni and Appiani liberatory maneuver for treatment of ageotropic horizontal canal benign paroxysmal positional vertigo: A prospective randomized trial - Jiyeon Lee; Dong‐Han Lee; Haemin Noh; Jung Eun Shin; Chang‐Hee Kim (Laryngoscope Investigative Otolaryngology, 2021)
Abstract Objective To examine the treatment effects of repositioning maneuvers with the head turned 45° downwards (Gufoni maneuver) and 45° upwards (Appiani maneuver) in 25 patients with ageotropic horizontal semicircular canal (HSCC) benign paroxysmal positional vertigo (BPPV). Methods Patients were randomly assigned to the Gufoni or Appiani maneuvers, and their immediate and short‐term efficacy was investigated. Results The immediate treatment response was successful in four of 16 patients who were treated with the Appiani maneuver and were not successful in any of the nine patients treated with the Gufoni maneuver. The patients who showed spontaneous resolution during follow‐up outnumbered the patients who showed resolution of ageotropic HSCC BPPV immediately after the repositioning maneuvers. Conclusion This study showed a very low immediate resolution rate of ageotropic HSCC BPPV after the Gufoni maneuver; this may be attributed to the less effectiveness of the Gufoni maneuver against debris that often exists in the canal side of the cupula. Another interesting finding was that the rate of spontaneous resolution during the follow‐up period was higher than that of immediate resolution after the repositioning maneuvers, which may support the recently proposed hypothesis that ageotropic positional nystagmus can also be evoked by causes other than the otolithic attachment on the cupula, such as a slight change in the biochemical composition of the inner ear fluids. Level of Evidence 3.